Performance and Dust Removal: A Field Study and Theoretical Analysis in the Arid Environment in Iraq (International Journal of Scientific Research in Science and Technology, 2026)
The effect of environmental elements such as dust buildup, tilt angle, wind and rain on solar panel efficiency, particularly in dusty regions like Iraq have been studied and monitored. The field study focused on two locations in Iraq: The Razzaza area, which is located between Karbala and Anbar governorate and the University of Kerbala. The findings shows that dust buildup significantly reduces panel efficiency by lowering the surfaces optical transmittance by up to 65% in just one month. Also, the results of the field study were consistent with the theoretical analysis; therefore, the geometrical losses have a much greater effect than the optical losses due to light reflection. The results showed as the tilt angle increased, dust accumulated decreased. Therefore, the highlight of this study was that it found that the optimal tilt angle for optimal performance in Iraq is between 30° and 35°, which maximizes efficiency while minimizing dust buildup. Additionally, during various months of the year, certain weather elements like wind and rain also aid in minimizing the amount of dust that accumulates on the panels. Moreover, the results of the simulation model used in this study support the idea that when the ambient temperature rises, particularly during the hot months of June, July, and August, the solar module’s maximum output power falls.